Asperger’s Syndrome in a Clinical Sample: Reasons for Referral and Comorbidity - Staykova, S; Terziev, D; Manolova, H; Hristova, M; Bistrian, A (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
Asperger’s Syndrome (AS) is an autism spectrum disorder without mental retardation and language delay. AS often remains unrecognized until these children fail to adapt to school or kindergarten. The comorbid psychiatric disorders, achieving clinical significance, were considered as another pathway to diagnosis. This study is aimed to elucidate the reasons for referral, the frequency and the kinds of comorbidities in a clinical sample of consecutive cases of children and adolescents with AS. To this objective, clinical records of children and adolescents, who have received a DSM-IV diagnosis of AS after multidisciplinary assessment in a given time period were reviewed. After excluding 3 cases due to insufficient information, 24 cases of children and adolescents with Asperger’s Syndrome (23 boys and one girl) were identified. The mean age at the time of assessment and receiving diagnosis was 9.6 yrs. (age range 4 to 17 years). In twenty-one (87%) of the cases the reason for referral was an episode of disorganized behavior following an attempt to enroll the child at school or kindergarten, and more rare referral occurred within the significant school transition period. In the remaining 3 cases, the reason for referral was a comorbid condition. Comorbid conditions identified at the moment of assessment include: ADHD documented in 4 cases, tics in 3 cases, obsessive-compulsive behaviors in 4 cases, Stereotypic Movement Disorder or Trichotilomania in 4 of the cases. Within the clinical sample, a priori expected to include relatively severe cases, a higher frequency of comorbidity was found as compared to the rates in the general population. Adjustment reactions and comorbidities occasioned the referral, while AS was diagnosed only after specialized multidisciplinary assessment.